Faithful republic : religion and politics in modern America - Preston, Andrew, 1973-; Schulman, Bruce J.; Zelizer, Julian E.; Berman, Lila Corwin, 1976- (Politics and culture in modern America., 2015)
Despite constitutional limitations, the points of contact between religion and politics have deeply affected all aspects of American political development since the founding of the United States. Within partisan politics, federal institutions, and movement activism, religion and politics have rarely been truly separate; rather, they are two forms of cultural expression that are continually coevolving and reconfiguring in the face of social change. Faithful Republic explores the dynamics between religion and politics in the United States from the early twentieth century to the present. Rather than focusing on the traditional question of the separation between church and state, this volume touches on many other aspects of American political history, addressing divorce, civil rights, liberalism and conservatism, domestic policy, and economics. Together, the essays blend church history and lived religion to fashion an innovative kind of political history, demonstrating the pervasiveness of religion throughout American political life. Contributors: Lila Corwin Berman, Edward J. Blum, Darren Dochuk, Lily Geismer, Alison Collis Greene, Matthew S. Hedstrom, David Mislin, Bethany Moreton, Andrew Preston, Bruce J. Schulman, Molly Worthen, Julian E. Zelizer.